O impacto do uso das tecnologias disruptivas da sociedade Informacional nas relações de trabalho: conformação da regulação normativa sobre inteligência artificial ao valor social do trabalho - Carvalho, Marina Morais de (2021)
There are countless transformations promoted by information technologies in the work domain, since the end of the twentieth century, emerging from the unrestrained advance of the use of these tools in the work environment. One of the main concerns is the evermore frequent introduction of technological machines and tools responsible for the automation and computerization of the production chain, which has started to raise doubts about the need to maintain jobs and the obsolescence of human labor in the face of efficiency, practicality, and economy of these technologies. The following question arises from this scenario: how can an effective protection system be developed for workers directly affected by the use of Artificial Intelligence in work relations? It is intended, therefore, to analyze the reflexes of the use of disruptive technologies of the informational society in the work environment, seeking protective responses to this work activity, increasingly present in the globalized world, as a way of preserving the dignity of the human worker, subjected to unknown and future risks. Therefore, the general objective is to study the reflexes of the use of disruptive technologies of the information society in the work environment, seeking protective responses to this work activity, which is increasingly present in the globalized world, as a way of preserving the worker’s dignity, subdued to unknown and future risks. Thus, we start from the hypothesis that the Labor Law must seek to protect the worker, even though there are no specific regulatory frameworks, and it is necessary to adopt professional qualification methods to ensure the right to work and give the guarantee to the constitutional precepts. In the development of the hypothetical-deductive argument, we will start from the broader assumption of recognizing the social value of work through job qualification, based on the idea that only through qualified labor will be the maintenance of human work in the long term possible, despite the imbrications of information technologies in today's labor relations. In the end, the study proposes a joint performance of all social actors, as a way to enable the construction of a social contract strengthened in fair, dignified, and sustainable work.